2023
DOI: 10.2174/1573406418666220816121912
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Potential Drug Targets for Protozoan Infections

Abstract: Background: Currently, protozoan infectious diseases affect billions of people every year. Their pharmacological treatments offer few alternatives and are restrictive due to undesirable side effects and parasite drug resistance. Objective: In this work, three ontology-based approaches were used to identify shared potential drug targets in five species of protozoa. Methods: In this study, proteomes of five species of protozoa: Entamoeba histolytica (E. histolytica), Giardia lamblia (G. lamblia), Trichomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, by enabling the quicker discovery of therapeutic targets, computational tools lead to an advancement in the drug development process [40]. The initial stage of creating medications involves the identification of promising targets, within Plasmodium falciparum (a type of protozoan) Essential proteins are thought to be the best targets for antimalarial treatment because there is the maximum chances that most drugs will interact with them [41]. Recent research found that Plasmodium falciparum has a total of 5,389 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, by enabling the quicker discovery of therapeutic targets, computational tools lead to an advancement in the drug development process [40]. The initial stage of creating medications involves the identification of promising targets, within Plasmodium falciparum (a type of protozoan) Essential proteins are thought to be the best targets for antimalarial treatment because there is the maximum chances that most drugs will interact with them [41]. Recent research found that Plasmodium falciparum has a total of 5,389 proteins.…”
Section: Discussionmentioning
confidence: 99%